GAMBARAN MOTIVASI IBU DALAM MEMBERIKAN IMUNISASI DASAR PADA BAYI DI DESA PERENG,PRAMBANAN, KLATEN - Endang Sawitri; Setianingsih; Rizky Setya Tama (MOTORIK Jurnal Ilmu Kesehatan, 2023)
Immunization is essential for the baby's body to be immune to disease. Basic immunization data for October 2021 in Klaten district: new complete basic immunization coverage reached 58.4% of the target of 79.1%. Parents or mothers of babies in the villages of Pereng, Prambanan, and Kladen have not had the awareness to participate actively in the baby immunization activities carried out at each posyandu. The huge support of the baby's family is required to immunize the baby. The purpose of this study is to fi nd out the motivation of mothers to give basic immunization to babies in the villages of Pereng, Prambanan, and Klaten. Quantitative- descriptive research design The population in this study was the total of mothers who had a baby between 0 and 12 months, totaling 31. Sampling technique using total sampling. Data collection tool using a questionnaire. Characteristically, the respondents were 31.3 years of age; the last education of the most respondents was up to the high school level of 19 people; the most common job is that of a housewife, with a total of 24 respondents. The most motivated mother in giving basic immunization to the baby has sufficient motivation (48%).